APPENDIX 1A: ENREGISTERED COPY OF POPE LEO X'S LETTER TO CARDINAL WOLSEY, 27 JUNE 1521 (ASV, REG. VAT. 1202, FOLS 109r–112v; OLD FOLIATION: 110r–113v). (4th September 2015) - Unknown
Abstract : This letter is compared in the notes with Leo's letter to Wolsey of 1 April 1521 printed by Rymer in Foedera. . ., VI. 193–194 (XIII. 739–742), which it replicates in parts, especially before n. 40, and is here designated R.